The structure of socio-political discourse in the information-type society - Talanova, Liudmyla H.; Shkvorchenko, Nataliia M.; Savchuk, Hanna V.; Zhaboruke, Irene A.; Dashkova, Kateryna V. (My University, 2022)
The electorate is an integral participant in political discourse, therefore, in order to study the ways of a linguistic embodiment of its motivating intention, it is necessary, first of all, to find out the starting positions, that is, those discourse positions that are relevant for solving the goal of forming a discourse in a public environment. The novelty of the research is determined by the fact that the analysis of the representation in the language of the incentive intentions of representatives of society predetermines the necessity to clarify the specifics of the communicative role of a representative of the electorate in political discourse. The authors note that it becomes important to clarify the essence of the electoral segment of political discourse, which appears as an environment for the implementation of the incentive intention of ordinary citizens. The authors see the determination of the relationship between the concepts of communicative intention and strategy as an important component of the theoretical apparatus of the research. In particular, based on the study of the available linguistic interpretations of the intention and strategy, a theoretical position has been developed, which is the basis for further analysis of the actualisation of the incentive intention in the speech of the electorate. The practical significance of the study is due to the fact that the study of the specifics of the lingual implementation of incentive intentions in the electoral segment of political discourse is due to: the important role of political discourse in the life of society, the property of a representative of the electorate to turn from a passive recipient into an active participant in political discourse, the availability of innovative communication technologies for all citizens to indicate their position.
Shkvorchenko Nataliia M. The structure of socio-political discourse in the information-type society / Nataliia M. Shkvorchenko, Liudmyla H. Talanova, Hanna V. Savchuk, Irene A. Zhaboruke, Kateryna V. Dashkova // ASTRA Salvensis, year X. – 2022. - no. 1. – P. 79-95.
Keywords: political linguistics; language orientation of a person; verbal forms; social interaction; discursive activity